Reproductive Characteristics of the Selected Cocoa (Theobroma cacao L.) Clones after Regenerated from the Somatic Embryogenesis Culture - Gibson, Entuni; Hollena, Nori; Rebicca, Edward; Ahmad Kamil, Bin Mohd Jaafar (Walailak University, 2021)
This study was conducted to evaluate the reproductive characteristics of 4 elite cocoa clones (MCBC1, PBC230, KKM22 and KKM4) propagated via somatic embryogenesis culture. From the findings, all clones have similar reproductive characteristics with clones from conventional grafted. However, only KKM4 clone from immature zygotic embryo culture produced the shortest staminode to style distance of 1.83 mm. This consequently influenced flower stability by reducing the efficiency of pollination by insects. It was found that this clone also has the highest number of flowers drop after anthesis (5 flowers) and lowest production of cherelle (5 cherelles).Further observation revealed that floral development from first bud visible (BBCH51) to flower anthesis (BBCH68) of all clones took around 31 days. These cocoa flowers which remained receptive soon after anthesis at 10 am (day-31)until the next day (day-32) suggesting 2 days’ period of receptivity.